2005
DOI: 10.5194/angeo-23-1013-2005
|View full text |Cite
|
Sign up to set email alerts
|

Slow shock interactions in the heliosphere using an adaptive grid MHD model

Abstract: Abstract.A one-dimensional (1-D), time-dependent, adaptive-grid MHD model with solar wind structure has been used in the past to study the interaction of shocks. In the present study, we wish to study some fundamental processes that may be associated with slow shock genesis and their possible interactions with other discontinuities. This adaptivegrid model, suitable for appropriate spatial and temporal numerical simulations, is used for this purpose because its finer grid sizes in the vicinity of the steep gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Though the free path of solar wind particles is of the order of 1 AU, which, strictly speaking, means that the solar wind is a collisionless plasma, the MHD approximation is often used in studying the processes in the solar wind. For example, Wu et al (2005) have used this approximation in the analysis of the evolution of slow shock waves and their interactions with other discontinuities in the heliosphere. The MHD approximation was utilised in most of the above-mentioned works by exploring the interaction of perturbations with MHD shock waves.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Though the free path of solar wind particles is of the order of 1 AU, which, strictly speaking, means that the solar wind is a collisionless plasma, the MHD approximation is often used in studying the processes in the solar wind. For example, Wu et al (2005) have used this approximation in the analysis of the evolution of slow shock waves and their interactions with other discontinuities in the heliosphere. The MHD approximation was utilised in most of the above-mentioned works by exploring the interaction of perturbations with MHD shock waves.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…They found that a FSS can be destroyed by a forward fast shock (FFS) that overtakes it from behind and the strength of a FSS is decreased by following an FFS. During the transition of a fast shock's overtaking a slow shock from behind, the slow shock might disappear temporarily (Wu et al, 2005a). The study of Wu et al (2005a) also shows that during the process of the merging of two slow shocks, a slow shock-like structure is formed first; later, the slow shock-like structure evolves into an intermediate shock-like structure.…”
Section: Introductionmentioning
confidence: 95%
“…During the transition of a fast shock's overtaking a slow shock from behind, the slow shock might disappear temporarily (Wu et al, 2005a). The study of Wu et al (2005a) also shows that during the process of the merging of two slow shocks, a slow shock-like structure is formed first; later, the slow shock-like structure evolves into an intermediate shock-like structure. This intermediate shock-like structure then evolves into an intermediate wave (IW) and a slow shock-like structure.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The interaction of a shock with a magnetic cloud, the interaction of two shocks, and the interaction of two clouds have also been numerically modeled in the last 10 years [14][15][16][17][18][19][20][21][22][23] . Different physical phenomena occur during the propagation of a second, faster CME overtaking a first, slower CME.…”
Section: Introductionmentioning
confidence: 99%